NICKEL-CONTAINING COMPOUNDS FOR THE CATALYTIC CONVERSION OF METHANE TO GAS SYNTHESIS - Begimova G.U.; Komashko L.V.; Tungatarova S.A. (Academic Scientific Journal of Chemistry, 2019)
In recent decades, many experiments have studied the catalytic materials synthesis’ that are active, selective and stable in the conversion of gaseous hydrocarbons to organic liquids. The resulting nickel-based catalysts are discussed in terms of their preparation, physicochemical characteristics, and internal properties that the conversion of methane to synthesis gas.